The Influence of Financial Attitude and Financial Knowledge on Saving Interest (Case Study on Students of Brigjend Katamso I Vocational High School Medan) - Etty Harya Ningsi; Lambok Manurung (Jurnal Mantik, 2021)
The research analysis aims to determine whether financial Attitude and Financial Knowledge partially and simultaneously affect the Interest in Saving (Case Study on Students of SMK Brigjend Katamso I Medan). The data analysis technique that are being used is the associative method with the help of the SPSS version 16.0 program. This study used multiple linear regression analysis. The sample in this study were 62 respondents. The primary data collection was using a questionnaire. The results showed that financial attitude had a positive and significant effect on interest in saving at SMK Brigjend Katamso I Medan. Financial Knowledge has a positive and significant effect on the interest in saving at SMK Brigjend Katamso I Medan. Financial Attitude and Financial Knowledge have a positive and significant effect on the interest in saving at Brigjend Katamso I Vocational High School Medan.